Spread of Spiritual Ideas of Shri Ramakrishna: The Influence of Shri Ramakrishna's Spiritual Ideas in the Modern World (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Sri Ramakrishna's spiritual message has without a doubt discovered its route 'home' all through the length and broadness of the cutting edge world, even among pragmatist and logical scholars. While his lessons have been tested, bantered about and scrutinized both in the East and the West, incomprehensibly, they are getting to be powerful in focuses of perfection and learning in science and innovation. Gregory Bateson, for instance, proclaims that 'encounters gave by the sense information are deceptions whereupon our civilisation is based'. Ramakrishna's 'reasoning of brain' is as yet progressive and subject to scrutinize by thinkers, neurologists, physiologists and others. Be that as it may, religious practices, religious fundamentalism and even religion itself, have positively been tested at their exceptionally establishments by the experiential existentialism of this Holy person, who has by his sheer limit with regards to 'love of Mother altered the spiritual mission of the twentieth century.